Biblioteca virtual como herramienta tecnológica y su aporte en el proceso de enseñanza y aprendizaje a los estudiantes de la Carrera de Psicología de la Universidad Técnica de Babahoyo - Loor Maldonado, Henoc Rodolfo (2019)
The proper use of the virtual library as a technological tool during the teaching – learning process is an important contribution in higher level students, since virtual libraries have reliable contents that allow user to develop not only academic tasks, but also cultural in professional preparation. Virtual libraries arise as a need for bibliographic order for research tasks, which when used as a technological tool plays a very important role in its information content, allowing access to a digital world whit the use of the internet. The role of teacher in the face of the challenges that education present, forces him to constantly train, is it there that virtual library because an ally in the teaching – learning process to achieve goals, which were previously established by the educator. The creation of a methodological guide is of great help to the teacher, since as mentioned above, it enables him to practice academic, making his classes more interactive and stimulating students.